Analisis Kesalahan Siswa dalam Menyelesaikan Soal Materi Segitiga Sembarang - Apriani, Diana; Sunardi, Sunardi; Rizta, Amrina (Universitas Muhammadiyah Palembang, 2019)
Triangular material is the subject matter that must be mastered by students before learning other mathematical material, one of which is the matter of building space. However, there are still many students who make mistakes in solving triangular material problems, especially arbitrary triangles. This study aims to find out what mistakes are made by students in solving arbitrary triangle material problems in class VIII of SMP Negeri 15. This type of research is a qualitative descriptive study. The subjects in this study were students of class VIII.1 and students of class VIII.2 which amounted to 66 students. Data collection techniques in the form of giving test questions totaling 5 questions essays. Based on the results of the research that has been carried out, 29 students with a percentage of 44% made a misconception, 20 students with a percentage of 30% made a procedure error and 8 students with a percentage of 12% did two types of errors namely misconceptions and procedural errors at once on each question.